Exploration of Lichenes in the Mutis Mount Area, Noepesu Village, West Miomaffo District - Kamaluddin, Kamaluddin; Hanoe, Emanuel MY; Sila, Vinsensia Ulia Rita (Advances in Tropical Biodiversity and Environmental Sciences, 2023)
This study aims to explore and identify the types of Lichenes that exist at the Mutis Mount Area, Noepesu Village, West Miomaffo District, and the Biology Education Laboratory, University of Timor. This research was conducted for 6 months starting from May-October 2022. This research is descriptive qualitative research. Sampling used a purposive sampling method. The collected Lichenes were identified based on their characteristics using the determination key and then matched with the photo collection. Morphological observation of lichenes was conducted at the Biology Education Laboratory, University of Timor using a microscope. The result of observations and collections based on this research conducted in the Mutis Mount area found 29 species of Lichenes with 12 families, the species found were  Septennium azureum, Parmotrema tinctorum, Parmotrema perlatum, Parmelia sulcate, Parmelia sp, Flavoparmelia afternoondians, Usnea hirta, Usnea sp 1, Pyxine subcinerea, Cryptothecia sp, Dirinaria sp, Lepraria Lobificans, Lepraria incana, Lepraria sp 1, Hydropunctaria maura, Candelariella sp, Arthonia ilicina, Arthonia Radiata, Arthonia Clemens, Graphis Scipta, Graphis sp1, Graphis sp2, Graphis sp3, Graphis sp4, Graphis sp5, Graphis sp6, Ramalina farinaceae, Cryptothechia striata, and Bacidia insularis . Lichenes were found in soil, weathered wood, tree trunks, and rocks with thallus morphology, namely Crustose, Foliose, Fructicose, and Squamulose.